2003
DOI: 10.1002/bit.10679
|View full text |Cite
|
Sign up to set email alerts
|

Novel type of in situ extraction: Use of solvent containing microcapsules for the bioconversion of 2‐phenylethanol from L‐phenylalanine by Saccharomyces cerevisiae

Abstract: A novel in situ product removal (ISPR) method that uses microcapsules to extract inhibitory products from the reaction suspension is introduced into fermentation technology. More specifically, L-phenylalanine (L-Phe) was transformed by Saccharomyces cerevisiae to 2-phenylethanol (PEA), which is inhibitory toward the yeast. In order to continuously remove PEA from the vicinity of the cells, the reaction suspension was brought into contact with capsules of 2.2-mm diameter that had a hydrophobic core of dibutyl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 34 publications
(38 reference statements)
0
28
0
Order By: Relevance
“…Etschmann and Schrader (2006) achieved the highest 2-PE concentration (10.2 g/L overall) reported by using K. marxianus CBS 600. Other ISPR techniques such as microcapsulation (Serp et al, 2003;Stark et al, 2003); and organophilic pervaporation (Etschmann et al, 2005) have also been reported.…”
mentioning
confidence: 97%
“…Etschmann and Schrader (2006) achieved the highest 2-PE concentration (10.2 g/L overall) reported by using K. marxianus CBS 600. Other ISPR techniques such as microcapsulation (Serp et al, 2003;Stark et al, 2003); and organophilic pervaporation (Etschmann et al, 2005) have also been reported.…”
mentioning
confidence: 97%
“…Moreover, the alginate may be gelled and clogged at the orifice of the nozzle if the flow rate of the solutions was not properly determined. Even so, the clogging issue could be avoided if vibration force was applied to the nozzle (Whelehan et al 2010;Marison et al 2004;Wyss et al 2004;Stark et al 2003).…”
Section: Co-extrusion Dripping Methodsmentioning
confidence: 98%
“…The tested neutralizing agents are Alamine-336 in oleyl alcohol and calcium carbonate (Lee et al 2013;Tik et al 2001). Since the capsules have low mass transfer resistance, the solutes/ions could be freely diffused between the inner liquid core and the fermentation media through the capsular membrane to react with the inhibitors (Lee et al 2013;Whelehan et al 2010;Marison et al 2004;Koyama and Seki 2004b;Chai et al 2004;Wyss et al 2004;Stark et al 2003). The neutralization could be achieved via liquid-liquid extraction (Whelehan et al 2010;Marison et al 2004;Wyss et al 2004Wyss et al , 2004Wyss et al , 2005Stark et al 2003).…”
Section: Lactobacili Fermentationmentioning
confidence: 98%
See 1 more Smart Citation
“…End-product inhibition occurs in many fermentation processes and in situ removal of them typically enhances product formation rates, yields, and specificity (Christen et al, 1990;Gyamerah and Glover, 1996;Qureshi et al, 1998). Techniques that have been employed for in situ removal of fermentation products include liquid-liquid extractive fermentation (Adrian et al, 2000), use of selective membranes (Chang et al, 1992), cell recycling (Roca and Olsson, 2003), adsorption (Millitzer et al, 2002), microcapsule application (Stark et al, 2003) and vacuum fermentation (Qureshi et al, 1998). However, the intimate contact of an organic phase with the broth implies that the organic components of this phase may be present in the aqueous www.intechopen.com phase at saturation levels.…”
Section: In Situ Extraction From the Biomass Of Microbial Fermentationmentioning
confidence: 99%